Social Identity of Buginese-Makassarese Migrant Student - Hasanuddin, Amalia Soraya; Setyawan, Jefri; Edy, Dewi Fatmasari (Utan Kayu Publishing, 2025)
The Bugis-Makassar tribes are two large tribes from South Sulawesi, Indonesia, renowned for their migration tradition. Many Buginese-Makassarese young people continue this tradition by seeking better educational opportunities outside their hometown. This study aims to explore the social identity of Buginese-Makassarese migrant students in foreign cities. Using a qualitative research design with a phenomenological approach and interpretive paradigm, data was collected through semi-structured interviews and analyzed using thematic analysis, which resulted in five key themes. The findings reveal that Buginese-Makassarese migrant students feel secure in revealing their social identity, as they maintain a positive balance in their relations with both ingroups and outgroups. They display strong cohesiveness and empathy when interacting within the ingroup and exhibit self-esteem, tolerance, and effective adaptation when engaging with the outgroup. Notably, the cultural values of siri’ na pacce—which emphasize dignity, empathy, and mutual support—play a crucial role in shaping their social identity and promoting psychological well-being. These values contribute significantly to the student’s self-concept and their ability to navigate complex social interactions in a new environment. This study provides valuable insights into how migrant students, particularly from the Buginese-Makassarese ethnic group, can adjust and maintain their cultural values while adapting to life in different cities.